The Citizenship Experiment Contesting the Limits of Civic Equality and Participation in the Age of Revolutions - Koekkoek, René (Studies in the History of Political Thought, 2019)
Focusing on the United States, France and the Dutch Republic in the revolutionary 1790s, The Citizenship Experiment explores the convergence and divergence of Atlantic citizenship ideals in light of the Haitian Revolution and the French revolutionary Terror. Readership: All interested in the history of the Age of Atlantic Revolutions, the American, French, Dutch, and Haitian revolutions, as well as the history of political thought, citizenship, and empire. Keywords are citizenship, revolution, Atlantic world, equality, participation, Haitian Revolution, Terror, rights, civilization, 1790s, exclusion, inequality, popular societies.